Impact of Nano Manganese and Siapton on the Growth of Fenugreek - Akhlass Mery Kadim Alkhlefawi (Al-Qadisiyah Journal For Agriculture Sciences, 2022)
A field study was conducted in a nursery in the Euphrates region, AL Qadisiyah Governorate of Iraq, to study the impact of the nano manganese and siapton fertilizer on the growth of Trigonella foenum-graecum L., The experiment was designed with randomized complete blocks,by factorial organization, and with three replications. It included 4 concentrations of nano manganese (0, 1, 2, and 3) g L-1 and 3 concentrations of Siapton (0, 2, and 4) ml L-1. After (90) days from the date of seed germination, the vegetative growth indicators were measured, while the properties of the oil were measured after 6 months from the date of sowing the seeds. The least significant difference (LSD) was used at the 0.05 probability level to test the differences between the means of the treatments. Results showed that the concentration of 2 g L-1 of nano Manganese showed superiority in increasing most of the studied parameters, which included (plant height, number of leaves, leaf area, leaf content of chlorophyll, and the percentage of Linoleic acid), and the impact of nano manganese was negative on the percentage of Palmitic acid. The concentration 2 m L-1 of Siapton fertilizer outperformed increasing plant height, chlorophyll content of leaves, and the percentage of unsaturated fatty acid Linoleic acid, and distinguishing a concentration of 4 m L-1 in achieving the largest number of leaves and the highest leaf area, and the impact of Siapton organic fertilizer was negative on the percentage of saturated fatty acid Palmitic acid. The interaction between the two factors showed the superiority of the combination of 2 g L-1 of nano manganese and 4 m L-1 of organic fertilizer Siapton in achieving the highest plant height, while the highest numeral of leaves, leaf area, chlorophyll content and percentage of Linoleic acid with the combination was 2 g L-1 of nano manganese and 2 m L-1 l. of organic fertilizer Siapton. The impact of the two interactions caused a significant decrease in the percentage of Palmitic acid.